Development and evaluation of the General Surgery Objective Structured Assessment of Technical Skill (GOSATS). Issue 12 (6th October 2019) - Halwani, Y; Sachdeva, A K; Satterthwaite, L; de Montbrun, S
Abstract: Background: Technical skill acquisition is important in surgery specialty training. Despite an emphasis on competency-based training, few tools are currently available for direct technical skills assessment at the completion of training. The aim of this study was to develop and validate a simulated technical skill examination for graduating (postgraduate year (PGY)5) general surgery trainees. Methods: A simulated eight-station, procedure-based general surgery technical skills examination was developed. Board-certified general surgeons blinded to the level of training rated performance of PGY3 and PGY5 trainees by means of validated scoring. Cronbach's α was used to calculate reliability indices, and a conjunctive model to set a pass score with borderline regression methodology. Subkoviak methodology was employed to assess the reliability of the pass–fail decision. The relationship between passing the examination and PGY level was evaluated using χ 2 analysis. Results: Ten PGY3 and nine PGY5 trainees were included. Interstation reliability was 0·66, and inter-rater reliability for three stations was 0·92, 0·97 and 0·76. A pass score of 176·8 of 280 (63·1 per cent) was set. The pass rate for PGY5 trainees was 78 per cent (7 of 9), compared with 30 per cent (3 of 10) for PGY3 trainees. Reliability of the pass–fail decision had an agreement coefficient of 0·88. Graduating trainees were significantly more likely to pass the examination than PGY3 trainees (χ 2 = 4·34, P = 0·037). Conclusion: A summative general surgery technical skills examination was developed with reliability indices within the range needed for high-stakes assessments. Further evaluation is required before the examination can be used in decisions regarding certification. Graphical Abstract: Competency-based training and assessment is receiving great attention in surgical education. The aim of this study was to develop and evaluate a general surgery summative assessment tool for senior trainees. With further study and confirmation, performance on this examination could help with decisions on surgical trainee certification. Discriminating technical skills examination